Australian Earthworms as a Natural Agroecological Resource - Blaskemore, R J; Paoletti, M (Annals of Arid Zone, 2016)
Australia has an unrealized natural resource in its unprecedented diversity of earthworms. Surveys on the ground and of the literature give a total for Australia (and Tasmania) of 715 species and sub-species in 73 genera and ten families, comprising 650 endemic natives, wholly adapted to Australian climates and soils, and 65 (ca. 9%) exotic interlopers that tend to be less specialized, but more widespread. Of the exotics, just one-third, about 3% of the total species, are lumbricids of the holarctic family Lumbricidae. If neo-endemics and translocated natives are included as non-natives, it raises their numbers above 80 species - higher than a previous "National Survey" estimate of just 27 species. Compared to any other region, the earthworm fauna of Australia is particularly diverse (e.g. India - 350 spp., New Zealand - 200 spp.; USA/Canada - 180 spp.; USSR - 113 spp.; Amazonia - >120 spp.; British Isles ca. 69 spp.) and, as much of the continent has yet to be systematically surveyed, it is anticipated that the tally of both natives and exotics will continue to grow many-fold. Earthworms are vital for sustainableprimary production and waste management, yet only slowly do we gain an ecological appreciation of their potential to benefit Australia’s natural environment. Experiments and field trials in Australia have tended to mimic those conducted overseas, especially in Europe, using a limited range of exotic species, with similarly variable results and have largely overlooked native species. A long-term project to import the exotic Aporrectodea longa from Tasmania to the mainland was somewhat compromised from the outset by the well-documented prior occurrence, not only of this species, but also of many other ’deep-burrowing’ species, on the mainland. However, it now seems that modifying soil to maintain or enhance conditions favorable for resident populations to recolonize and expand may prove the most Â·beneficial option for both worm and farmer. Appropriate management strategies are briefly presented.